Atividade de Xantina-oxidase na Carcinogênese Induzida pela 1.2-dimetil-hidrazina - Affonso, Ottilia R. (2023)
Colon tumors were induced in aduitmale rats by weekly s.c. injections of 1,2-dimethylhydrazine (DMH) ata dose of20 mg/kg body weight for 20 weeks. The XO and XD activities were measured as a function of position along the length of the intestine. Animals injected with DMH showed enzyme activity reduced when compared to normal Controls. An increase in XD activity was shown in blood serum of animais treated with DMH.